Creative play: integrating art into playgrounds a typology - Gerth, Allison R. (Kansas State University, 2011)
Children are imaginative, creative, and active. Children of all age groups are influenced by their surroundings, particularly school-aged children (Frost, 2010). School-aged children’s physical, emotional, social, and intellectual developmental characteristics are influenced by their surrounding environments. Today, uniform playgrounds are diminishing the opportunities for youth to develop their personal creativity and imagination through play (Thompson 2007, Solomon 2005). By integrating art into playgrounds, these environments will offer children greater opportunity for developmental enrichment through their interactions with the site. Researched cases of art and play have inspired the development of a typology. The typology is a collection of quintessential ways that settings for play can be visually and experientially enriched by art. This process began with three critical questions; 1) What constitutes a playground? 2) What is art? and 3) How can art be integrated into playgrounds? More than 30 precedents that demonstrate art in a play setting were examined. Noting differences and similarities between the precedents, 12 types were identified. Next, analysis matrices identifying primary and, if applicable, secondary placement of each of the precedents in the 12 developed types, including sub-types, giving art in playgrounds a place. Also classified was type of art, high or vernacular, for each precedent. The research methodology was an iterative process of literature and precedent research followed by the distillation of types, further research, and refinement of the typology framework.
Keywords: Childhood Development; Art; Playgrounds; Typology; Art + Play; Playground Design; Landscape Architecture (0390)